Using dictation to improve listening skills of grade 10 students at a high school in Ha Nam province - Nguyễn, Thị Quỳnh Anh (2020)
How to improve English listening skill effectively is always a topic that has attracted much attention from language teachers. Students of English find listening lessons difficult because they do not have appropriate methods to get over the difficulties. As a result, this research attempts to look at one method called dictation to improve high school students‟ listening skills. This study is conducted to find out: (1) a clear view of dictation, (2) how the method works on thestudents,and(3) how much the student‟s listening skills are improved.The data were collected through action research with 40 grade 10 students in a local high school in Ha Nam province. All of the groups were pre-tested at the beginning of the study. Throughout the learning process in class for 18 weeks, the teacher gave the students dictation practice tasks. All students in the class were post-tested at the end of the intervention. For thedetailed outcome, the data was collected and analyzed carefully. An analysis of survey questionnaires is done on the students to find out their attitudes towards this technique. As the findings show, the research reveals that dictation contributes positively to improving listening skills for students